2013
DOI: 10.2304/elea.2013.10.4.357
|View full text |Cite
|
Sign up to set email alerts
|

Constellations of Support and Impediment: Understanding Early Implementation Dynamics in the Research and Development of an Online Multimodal Writing and Peer Review Environment

Abstract: In this article, the authors trace teachers' experiences while participating in an educational technology development and research project focused on the creation and use of an online writing and peer review environment. They follow teachers from their initial expectations of the program, to their response to professional development training sessions, planning sessions, student account setup, and to their initial attempts at utilizing the digital learning environment in the classroom. In so doing, the authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…For teachers with one to four years’ experience of previous training, the use of DST in instruction increases from 67% to 100%. These data continue to show the importance of long‐term technology‐supported professional development (Olmanson & Abrams, ). More importantly, they offer guidance to districts on the number of workshops teachers might need before implementing DST projects.…”
Section: How and Why Teachers Use Dstmentioning
confidence: 86%
See 2 more Smart Citations
“…For teachers with one to four years’ experience of previous training, the use of DST in instruction increases from 67% to 100%. These data continue to show the importance of long‐term technology‐supported professional development (Olmanson & Abrams, ). More importantly, they offer guidance to districts on the number of workshops teachers might need before implementing DST projects.…”
Section: How and Why Teachers Use Dstmentioning
confidence: 86%
“…Such teacher‐external factors, including availability and access to technology, need to be addressed at the district level and have a significant influence on the level and quality of classroom technology use. A study by Olmanson and Abrams () on an online multimodal writing program revealed that teachers’ implementation efforts are contingent upon complex and interrelated factors, including access, administrator support, and district priorities. Likewise, other studies noted that teacher interest in technology integration is closely linked to availability of resources, curricular or cultural alignment, and technical support and training (Rohaan, Taconis, & Jochems, ; Schifter, ), all of which ultimately are tied to district initiatives.…”
Section: What Is Dst?mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the late 1990s, teachers have worked to integrate new media and aspects of new literacies into the curriculum. The range of integration rationales includes an interest in leveraging platform affinity and novelty to inject excitement into content areas (Olmanson and Abrams 2013), rethinking student participation in learning spaces (Vasudevan 2010), encouraging the expression of student identities (Rust 2015), closing the digital divide, and mirroring collaborative ecologies of the twenty-first-century workplace and better facilitating the inclusion of multimodality in academic texts to fulfill evolving State and national expectations (Olmanson et al 2015).…”
Section: New Media Literacies In Schoolsmentioning
confidence: 99%
“…Regardless, when students write and revise, their process is shaped by the affordances of their writing platforms. As increasingly ubiquitous digital tools align the in-school composition process with out-of-school processes (Olmanson and Abrams 2013) it is important to consider the relationship between writing platforms and the work they support.…”
Section: Technologies For Evaluating and Revising Writingmentioning
confidence: 99%